Agroecological Consumption as Activism: Fair of the Faculty of Agronomy of the City of Buenos Aires - Muzlera, Jose (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
In order to describe the profile of consumers of agro-ecological foods and understand their motivations, we carried out 21 semi-structured interviews and a survey of 234 people at the Producer-to-Consumer Fair at the School of Agronomy of the University of Buenos Aires. In this article, the main features of the consumers are presented. The most important conclusion is that those who buy these foods are people from the urban middle class, with a higher than average level of formal education, and that consumption is motivated not only by associating them with a healthier life and a better quality of life, but also because they see in this practice a political and solidarity action.